Component-Based Refactoring of Parallel Numerical Simulation Programs: A Case Study on Component-Based Parallel Programming - Carvalho Junior, Francisco Heron de; Rezende, Cenez Araujo (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2011)
Component-based programming has been applied to address the requirements of large scale applications from sciences and engineering with high performance computing (HPC) requirements. However, parallelism has been poorly supported in usual component infrastructures. This paper evidences the efficacy of an HPC platform of parallel components for development and execution of numerical simulation code, mostly found in these applications.